Voice outcomes following treatment of benign midmembranous vocal fold lesions using a nomenclature paradigm. (25th September 2015) - Akbulut, Sevtap; Gartner‐Schmidt, Jackie L.; Gillespie, Amanda I.; Young, VyVy N.; Smith, Libby J.; Rosen, Clark A.
Abstract : Objectives/Hypothesis: Benign midmembranous vocal fold lesions (BMVFLs) are common voice disorders, but interpretation of outcomes following treatment is difficult due to the lack of a standardized nomenclature system for these lesions. Outcome results are increasingly important to third party payers. This study aimed to investigate the outcomes of patients with BMVFLs using a previously validated nomenclature, and to provide incidences and outcome results for each diagnosis. Methods: A retrospective chart review of BMVFL patients was performed. Treatment was individualized but typically involved implementation of nonsurgical therapy followed by phonomicrosurgery as needed. A previously reported BMVFL stratification system was used. Results: A total of 224 patients with BMVFLs were studied. Sixty‐seven percent of all patients with a BMVFL underwent phonomicrosurgery. The most common BMVFL types were polyp and nonspecific vocal fold lesion. Pseudocyst represented 0.9% of the cohort. The Voice Handicap Index‐10 (VHI‐10) and acoustic data demonstrate a high degree of treatment success. The mean change in VHI‐10 was greatest for cyst–subepithelial and polyp. Fibrous mass–ligamentous patients had the smallest mean change in VHI‐10. Mean post‐treatment VHI‐10 scores of all the lesions except fibrous mass–ligamentous were within normal limits (<11). Conclusions: This study represents the first outcomes‐based report of BMVFLs using a strictly defined nomenclature system for stratification of lesions. Ligamentous fibrous mass lesions have a decreased response to treatment compared to all other lesions. This study demonstrates the ability to return most BMVFL patients to normal speaking voice capabilities following treatment. Level of Evidence: 4. Laryngoscope, 126:415–420, 2016